Implementasi Just In Time dan Pengaruhnya terhadap Kinerja Operasional dan Kinerja Perusahaan Manufaktur di Kota Makassar (Studi pada Kawasan Industri Makassar) - serang, Serlin (Jurnal Aplikasi Manajemen, 2012)
This research was conducted in the manufacturing companies in the Makassar industrial zone (Kawasan Industri Makassar, KIMA) in the municipality of Makassar. Data are collected using questionnaire with Likert scale. Respondents are required to report their perception on the implementation of JIT purchasing, JIT production, JIT selling, operational performance and organizational performance. Research hypotheses are analyzed using path analysis.The findings of this research show that proper implementation of JIT purchasing and JIT selling can improve operational performance and organizational performance. JIT production does not directly influence organizational performances, howevers JIT productioncan improve organizational performance through operational performance. This would mean that JIT production can have a greater role in improving operational performance as a manifestation of the better implementation of JIT production.